Guidelines for Product Placement on Digital Television: Consumer Protection vs Survival of Television Operators - Chaisuwan, Bu-nga; Kuldilok, Panpilas; Sakuna, Chachaya; Chanesirirattanakorn, Thitirat (Journal of Digital Communications, 2024)
This research aims to study the formats of product placement on digital television, explore opinions of stakeholders on the guidelines for product placement, and identify guidelines for product placement in conformity with the NBTC’s regulations from the perspective of consumer protection. As a mixed method research, various research methods were employed, including documentation analysis, product placement content analysis, in-depth interviews, survey research, social laboratory research, and panel discussions. The research found that product placement formats on digital television are different from theories in the past. Currently, there are five forms of product placement on digital television, namely product mention, product presence, product experience, product for sale, and supportive VTR. From stakeholders’ opinions, appropriate product placement on digital television should align with program objectives, structure, audience preferences, and ensure factual accuracy. Duration, quantity, and picture size of the advertisement should also be considered. The guidelines for product placement on digital television that conform to the NBTC’s regulations should consider these five factors, namely, types of programs, types of products, formats of general product placement, suitable formats for each type of program, and audience notification on product placement.